Polyphyllin Ⅲ-Induced Ferroptosis in MDA-MB-231 Triple-Negative Breast Cancer Cells can Be Protected Against by KLF4-Mediated Upregulation of xCT - Zhou, Yulu; Yang, Jingjing; Chen, Cong; Li, Zhaoqing; Chen, Yongxia; Zhang, Xun; Wang, Linbo; Zhou, Jichun (Frontiers in Pharmacology, 2021)
Ferroptosis, which is characterized by the accumulation of intracellular iron and subsequent lipid peroxidation, is a newly discovered form of regulated cell death and plays an important role in tumor suppression. Herein, we showed that Polyphyllin III, which is a major saponin extracted from Paris polyphylla rhizomes, exerted its proliferation-inhibitory effect on MDA-MB-231 triple-negative breast cancer cells mainly through ACSL4-mediated lipid peroxidation elevation and ferroptosis induction. ACSL4 deletion partly attenuated Polyphyllin III-induced ferroptosis. Polyphyllin III treatment also induced KLF4-mediated protective upregulation of xCT, which is the negative regulator of ferroptosis. Interestingly, combination with the xCT inhibitor sulfasalazine (SAS) or downregulation of KLF4 sensitized MDA-MB-231 cells to Polyphyllin III. Furthermore, in vivo xenograft models, SAS significantly sensitized MDA-MB-231 breast cancer cells to Polyphyllin III, likely by enhancing intracellular lipid peroxidation and ferroptosis. The results of this study collectively demonstrated that Polyphyllin III exerts its anticancer effect by inducing ferroptosis via ACSL4 in MDA-MB-231 breast cancer cells. More importantly, we observed for the first time that KLF4-mediated xCT upregulation serves as negative feedback during ferroptosis progression, which might contribute to drug resistance in cancer treatment.